2021
DOI: 10.1002/app.50869
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic improvement of mechanical and thermal properties in epoxy composites via polyimide microspheres

Abstract: Achieving synergetic improvements of mechanical strength, toughness, and thermal stability of epoxy resin has been a crucial but very challenging issue. Herein, to explore a new solution for circumventing this issue, polyimide microspheres were successfully prepared through the inverse nonaqueous emulsion process, and the structure, size distribution and morphologies of polyimide (PI) microspheres were comprehensively investigated. Then the PI microspheres were incorporated in epoxy resin matrix to systematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Moreover, if the majority of amide groups on the PAA chain are cured with EP at a relatively low temperature, then there are fewer amide groups left for imidization to form PI, and the expected superior thermally stable PI-EP copolymer matrix will not be obtained. Previous studies [ 17 , 18 , 19 , 20 , 27 , 28 , 29 , 30 ] reported that the PI-EP copolymer matrix could be obtained as expected, and benefits from both PI and EP have been observed. There must be some critical points worth noticing in the process of copolymerization.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Moreover, if the majority of amide groups on the PAA chain are cured with EP at a relatively low temperature, then there are fewer amide groups left for imidization to form PI, and the expected superior thermally stable PI-EP copolymer matrix will not be obtained. Previous studies [ 17 , 18 , 19 , 20 , 27 , 28 , 29 , 30 ] reported that the PI-EP copolymer matrix could be obtained as expected, and benefits from both PI and EP have been observed. There must be some critical points worth noticing in the process of copolymerization.…”
Section: Introductionsupporting
confidence: 62%
“…Since PI was polymerized from aromatic dianhydride and aromatic diamines, the terminal groups could be either amine or anhydride. These two terminal groups of PI could serve as good functional groups in hardening EP resin [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The variation of tensile strength can be attributed to the higher filler loading, the filler dispersion, and the filler–rubber interactions. , In this work, the microspheres (without surface modification and connected to the matrix without chemical bonds) are directly added into the SR matrix, and the interfacial adhesive between EM and the SR matrix is relatively weak [Figure c­(i–iii)]. The poor interfacial property is detrimental to transfer stress. , As a result, although the tensile strengths of the ITPMs are increased compared with that of S0, a slight decreased trend of tensile strength is observed when the EM content is over 6phr. Differently, the elongation at break of the ITPM increases consistently with the increasing content of EM.…”
Section: Results and Discussionmentioning
confidence: 86%
“…The poor interfacial property is detrimental to transfer stress. 40,41 As a result, although the tensile strengths of the ITPMs are increased compared with that of S0, a slight decreased trend of tensile strength is observed when the EM content is over 6phr. Differently, the elongation at break of the ITPM increases consistently with the increasing content of EM.…”
Section: Resultsmentioning
confidence: 93%
“…Over the past a few decades, toughening epoxy and maintaining its high strength at the same time have always been an important subject. 8–10 A practical approach to toughen epoxy resins is to use thermoplastics with high glass transition temperature, excellent thermal stability and toughness, such as polysulfone (PSF), 11–13 poly(ether sulfone) (PES), 14–16 polyimides (PI) 17–19 and poly(ether imides) (PEI). 20–22 PEI with excellent mechanical properties can effectively improve the toughness of epoxy resin without sacrificing other properties of epoxy resin and has been widely used as the modifier of epoxy resin.…”
Section: Introductionmentioning
confidence: 99%